Lu2O2S:Tb3+, Eu3+ nanorods: luminescence, energy transfer, and multicolour tuneable emission. Issue 39 (13th September 2016) - Zhang, Bowen; Zou, Haifeng; Guan, Hongxia; Dai, Yunzhi; Song, Yanhua; Zhou, Xiuqing; Sheng, Ye
Abstract : Bright and tunable color emission can be realized in uniform rod-like Lu2 O2 S:Tb 3+, Eu 3+ phosphors. Abstract : A series of Tb 3+ and Eu 3+ singly-doped and co-doped rod-like Lu2 O2 S phosphors have been synthesized via a facile hydrothermal method followed by a subsequent calcination process. The phosphors, with excellent dispersion and uniform rods, exhibit the characteristic Tb 3+ or/and Eu 3+ emissions with the strongest peaks located at 544 nm (green) and 626 nm (red), respectively. Moreover, the emission intensities of both Tb 3+ and Eu 3+ remarkably vary with increasing Eu 3+ incorporation, and as a result, bright and tunable color emission can be realized in the single-phase Lu2 O2 S host by varying the ratio of Eu 3+ to Tb 3+ ions. In addition, the multicolor luminescence of Tb 3+ and Eu 3+ co-doped rod-like Lu2 O2 S phosphors can be readily achieved by changing the excitation wavelengths. The energy transfer from Tb 3+ to Eu 3+ ions in Lu2 O2 S was systematically investigated in detail. These results prove that the as-synthesized Lu2 O2 S nanorods are an excellent host for rare earth luminescence, and the Lu2 O2 S:Tb 3+, Eu 3+ nanorods with tunable multicolor luminescence properties may have potential applications in the fields of full-color displays, solid-state light and field emission displays.